2021
DOI: 10.31235/osf.io/rc3kq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic review of studies considering grandparenting, health, and well-being

Abstract: Background and Objectives: Whether grandparenting is associated with improved health and well-being among older adults is a salient question in present-day aging societies. This systematic review compiles studies that consider the health and well-being outcomes of grandparenting, concerning (i) custodial grandparent families, where grandparents are raising children without parental presence; (ii) three-generation households, where grandparents are living with adult children and grandchildren; and (iii) non-cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 55 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…We expected larger interindividual differences in grandparents because life events differ in their impact on daily life and in the degree to which they are perceived as meaningful or emotionally significant (Doré & Bolger, 2018;Luhmann et al, 2020). Another reason for expecting heterogeneity in the individual trajectories were the considerable differences between grandparents in the amount of grandparental investment (e.g., Danielsbacka et al, 2022) and competing role demands (e.g., Arpino & Bellani, 2022) present in our samples. Our results, however, indicated that interindividual differences were larger in the controls than the grandparents for many models, or not significantly different between groups.…”
Section: Interindividual Differences In Changementioning
confidence: 90%
See 3 more Smart Citations
“…We expected larger interindividual differences in grandparents because life events differ in their impact on daily life and in the degree to which they are perceived as meaningful or emotionally significant (Doré & Bolger, 2018;Luhmann et al, 2020). Another reason for expecting heterogeneity in the individual trajectories were the considerable differences between grandparents in the amount of grandparental investment (e.g., Danielsbacka et al, 2022) and competing role demands (e.g., Arpino & Bellani, 2022) present in our samples. Our results, however, indicated that interindividual differences were larger in the controls than the grandparents for many models, or not significantly different between groups.…”
Section: Interindividual Differences In Changementioning
confidence: 90%
“…Research on well-being and health has found evidence for both role strain theory and role enhancement theory depending on the degree of grandparental role investment (Danielsbacka et al, 2022;Kim et al, 2017). Whereas no investment or being a grandchild's primary caregiver are associated with adverse effects in most studies, there is evidence that moderate levels of grandchild care have beneficial life satisfaction and health effects for noncoresiding grandparents.…”
Section: Grandparenthoodmentioning
confidence: 99%
See 2 more Smart Citations